ANALISIS PENDAPATAN DAN KELAYAKAN USAHATANI KELAPA DALAM DI KELURAHAN DONDO KECAMATAN AMPANA KOTA KABUPATEN TOJO UNA-UNA - S, Mohammad Ali (AGROTEKBIS, 2017)
The purpose of this research is to know (1) how big does the farmer income of coconut in the Village of Dondo, Ampana District, Tojo Una-Una Regency, (2) The feasibility of the farming of Coconut in The Village of Dondo, Ampana District, Tojo Una-Una Regency. The research was carried out in The Village of Dondo, Ampana District, Tojo Una-Una Regency in April to June 2016. 30 farmer respondents were taken from the total population of as many as 96 farmers by using the method of simple random sampling. The analysis showed that the income obtained by the farmer of coconut in the Village of Dondo, Ampana District, Tojo Una-Una Regency is Rp. 5.728.724, 92, the average acceptance of the farmer of coconut obtained once in 4 (four) months, or by Rp. 1.432.181, 23 every month. It is still relatively small compared with Central Sulawesi Minimum Regional Salary in the year 2016 of Rp. 1.670.000 every month. This means that the coconut farmers in The Village of Dondo need to find other revenue outside the farming in order to meet the needs of life and his family. The value of the farming of coconut in The Village of Dondo, Ampana District, Tojo Una-Una Regency is equal to 2,57, this value obtained from the division between income and the total cost. The value 2,57 means that every additional Rp. 1 the cost can generate revenue amounting to Rp. 2,57, this meant the farming coconut in the Village of Dondo is appropriate to be cured Keywords: Coconut, feasibility, income.